STUDY ON THE OPTIMIZATION OF MULBERRY LEAF EXTRACT BY MACERATING ETHANOL AND MICROWAVE ASSISTED EXTRACTION METHOD (MAE) WITH NATURAL DEEP EUTECTIC SOLVENTS (NADES) - Kunaedi, Aan; Indawati, Iin; Karlina, Nina; Fadhillah, Zakie; Cantika, Citra Dhea; Khulfiah, Ade Ayu (Universitas Muhammadiyah Magelang, 2023)
Ethanol extract from the leaves of Morus alba, an herb, has been widely used for medicine, including commercial formulations. This study aims to compare the characteristics of NADES extract using the MAE method and the maceration method. Mulberry leaf simplicia (Morus alba. L) ethanol extract was made with various ethanol concentrations of 50%, 60%, 70%, 80%, and 90%, and NADES (Natural Deep Eutectic Solvents) extract with a solvent ratio of 1:20 and 1: 30 on the MAE (Microwave Assisted Extraction) method with a time of 5 and 10 minutes. Measurement of total flavonoid content and total phenolic content was carried out by UV-vis spectrophotometry with quercetin and gallic acid as reference standards. The results showed that the ethanol extract with ethanol concentrations of 50%, 60%, 70%, 80%, and 90% had an average total flavonoid content; and total phenolic: 0.73%, 0.9%, 1.32%, 1.18%, 0.77%; total phenolic 96.789 mg/g, 71.262 mg/g, 126.465 mg/g, 116.643 mg/g, 93.366 mg/g. NADES extract with a solvent ratio of 1:20 at MAE 5